2022
DOI: 10.21203/rs.3.rs-1302296/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heavy metal in honey bees, honey and pollen produced in different locations of Konya province in Turkey

Abstract: We investigated the levels of heavy metals in honey bee, honey and pollen samples obtained from different locations of Konya City in Turkey. Five honey-bee colonies were placed in eight different locations, four of them around the city center and four in rural areas, in the province of Konya City in Turkey. Heavy metal (Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) levels were determined in honey-bee, honey, and pollen samples taken from these colonies, with comparison between samples from urban and rural areas. The val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In honey production, quality of honey, which is in uenced by many factors, is just as important as yield. It has been reported that the most commonly produced and consumed products among bee products are honey and pollen, which are sources of food and healing, and the presence of undesirable properties in these products can reduce the nutritional value of these products and human damage health (Bayır 2019). Sancak et al (2013) reported that Türkiye produces the best honey in the world due to the large number of ower species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In honey production, quality of honey, which is in uenced by many factors, is just as important as yield. It has been reported that the most commonly produced and consumed products among bee products are honey and pollen, which are sources of food and healing, and the presence of undesirable properties in these products can reduce the nutritional value of these products and human damage health (Bayır 2019). Sancak et al (2013) reported that Türkiye produces the best honey in the world due to the large number of ower species.…”
Section: Introductionmentioning
confidence: 99%
“…Bayır 2019;Boistean et al 2021). It has been found that the color of honey can change from yellow and amber tones, from a colorless white to a dark red, and this change is due to the botanical origin of the honey, the composition of the nectar, the harvesting process, the temperature and the storage duration (Sha ee et al 2013; Becerril-Sánchez et al 2021).…”
mentioning
confidence: 99%